Assembly and annotation of a mitochondrial genome of kinetoplastid protist Perkinsela. - David, Vojtěch (Jihočeská univerzita, 2013)
This thesis is based on a collaborative project between Laboratory of Molecular Biology of Protists led by Prof. Julius Lukeš and the laboratory of John Archibald (Department of Biochemistry & Molecular Biology, Dalhousie University, Canada). My contribution to the project, as the name of the thesis suggests is to process DNA and RNA sequencing data from Neoparamoeba pemaquidensis isolate that correspond to the mitochondrion of Perkinsela, also called Ichthyobodo-related organism (IRO). The main aim is to characterize mitochondrial gene content and to attempt to understand the mechanism of U-insertion/deletion RNA editing in Perkinsela and its evolution.
Assembly and annotation of a mitochondrial genome of kinetoplastid protist Perkinsela.
Keywords: Prkinsela; Perkinsiella; IRO; Ichthyobodo-related organism; gemone; RNA editing; mitochondrie; kinetoplast; endosymbiont; Neoparamoeba pemaquidensis; Prkinsela; Perkinsiella; IRO; Ichthyobodo-related organism; gemone; RNA editing; mitochondria; kinetoplast; endosymbiont; Neoparamoeba pemaquidensis